National accounts statistics : analysis of main aggregates, 1983/1984 - United Nations (New York : United Nations, 1986)
Tables present in this volume include analysis of data on gross domestic product (GDP) or net material product (NMP) by various structural components as well as other main income aggregates, based on current and constant prices for some or all of the years 1970 to 1984.
ne 17/07/2019
Ref
Keywords: National income